E-Coupons Event Management System (ECoMS) Using QR code in UiTM Tapah / Anis Syahirah Mohd Salim - Mohd Salim, Anis Syahirah (2019)
The key success of event is appropriately managing the event especially the attendance of the participants. Therefore, E-Coupons Event Management System (ECoMS) using QR Codes in UiTM is basically focused on event management system that provide platform for attendance to be monitor via mobile phone and web-based application. ECoMS has been carried out because of the difficulties in managing the event especially in tracking the student attendance for each event. The ECoMS has been developed to evaluate the effectiveness of event management system in recording realtime attendance during the event had occured in university. Besides, this project has adaptation of current technology using QR code scanner via students' smartphone. The evolution of this technology will ease the Student Welfare staff department during registration and managing the event in UiTM Tapah through merit nation system systematically. E-Coupons Event Management System (ECoMS) allows for collecting the attendance information via Android which will be calculated by using merit point. This project has been evaluated by survey among 150 students of the UiTM Tapah who are experienced attending the events. This evaluation is to measure the effectiveness of the development event management system in the campus. As the result show there are 89.5% of the respondents are satisfied with this project and recommended this system to be implement in the UiTM Tapah. This ECoMS can be improvised by providing finding or searching for the students who are qualified to get hostel in every semester based on the total of attendance events that the students have attended.